Fuzzy Employee Placement Suitability Assessment using Mamdani Fuzzy Method - Afriany, Renny; Sinaga, Rudolf; Samsinar, Samsinar (BERKALA SAINSTEK, 2022)
For a company, employees are the spearhead for the company because they have a function as Customer Service, customer satisfaction is obtained after interacting with the company through the performance of its employees. Employees are expected to meet all customer needs with the applicable regulations in the company and become a source of income for the company. To get reliable employees, one way is to assess the suitability of their placement in the appropriate position. With the assessment of the suitability of positioning, companies can consider and determine the provision of rewards, promotions, punishments, training, coaching, counseling, or transfers for their employees. The choice of method used to assess the suitability of employee placement in a company is Fuzzy Mamdani. With the Fuzzy Mamdani method, a system that is completely measurable and human assessments that tend to be immeasurable can be bridged. Assessment of the suitability of employee placement using the resulting fuzzy method, is expected to be an alternative solution for companies to give positions to their employees.